2019
DOI: 10.1177/0146621618824855
|View full text |Cite
|
Sign up to set email alerts
|

Linking With External Covariates: Examining Accuracy by Anchor Type, Test Length, Ability Difference, and Sample Size

Abstract: Research has recently demonstrated the use of multiple anchor tests and external covariates to supplement or substitute for common anchor items when linking and equating with nonequivalent groups. This study examines the conditions under which external covariates improve linking and equating accuracy, with internal and external anchor tests of varying lengths and groups of differing abilities. Pseudo forms of a state science test were equated within a resampling study where sample size ranged from 1,000 to 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Furthermore, the precision of linking estimates can be improved by including further person covariates in the analysis (Albano and Wiberg 2019;Sansivieri and Wiberg 2019). This could be particularly true if there also exist DIF effects for person covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the precision of linking estimates can be improved by including further person covariates in the analysis (Albano and Wiberg 2019;Sansivieri and Wiberg 2019). This could be particularly true if there also exist DIF effects for person covariates.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in their study indicated that even if the composition of the group taking the exam changes, test results can be controlled. In the study conducted by Albano and Wiberg (2019), in which gender was used as a common variable, it was determined that frequency estimation gives less error in the presence of anchor test and covariate variables. Moreover, recent studies comparing NEAT and NEC designs show that common variables can be used instead of common items.…”
Section: Studies Comparing Neat and Nec Designmentioning
confidence: 99%
“…However, specifically in examinations that are applied several times in a year or term, using the same anchor test sometimes can cause some problems; for example, the use of the same items repeatedly can lead to recall of items for individuals, which can negatively affect discrimination. Recently, as a solution to this problem, there are studies suggesting that test equating can be conducted by using nonequivalent groups with covariates (NEC) design (e.g., Akın Arıkan, 2020; Albano & Wiberg, 2019;Branberg, 2010;Branberg & Wiberg, 2011;Gonzales et al, 2015;Wiberg & Branberg, 2015;Wiberg & von Davier, 2017). For example, Yurtçu (2018) equated scores obtained from different tests by using common item scores, gender, and mathematics self-efficacy scores as covariates.…”
Section: Introductionmentioning
confidence: 99%
“…When neither single group nor random groups designs are feasible, it may be possible to use a set of common items (sometimes called an anchor test ) as a form‐invariant connective. This design, denoted common‐item nonequivalent groups design , is widely used in large‐scale testing (Albano & Wiberg, 2019; Kolen & Brennan, 2013). Here, scores on the anchor test are considered comparable regardless of the form on which they appear.…”
Section: Connectivesmentioning
confidence: 99%